Rethinking sons and daughters: Shifting gender preferences among Chinese Indonesian families (1998-1999) - Donie Fadjar Kurniawan; Purwoko Ajie (Jurnal Sosiologi Dialektika, 2026)
This study aims to describe the perceived value of boys and girls within Chinese families in Surakarta during 1998-1999 and to explore similarities and differences across socioeconomic categories: Traders versus Professionals; Single working Fathers versus Working Mothers and Fathers; New Families, Families with Children, Families with Children and Grandchildren; and The Poor versus The Rich. The research employs an emic approach and involves fourteen Chinese families meeting the criteria for these categories. Data were collected through personal observation and in-depth interviews with married couples. Data analysis was conducted interactively through processes of reduction, interpretation, and conclusion-drawing in a circular manner. The results indicate that male and female children are generally regarded as equal in value, differing only in the description of their roles. Traditional views on the superiority of male children are seen as outdated. The perspectives of traders and professionals have shifted from traditional to modern views on gender, while families with both working parents exhibit egalitarian principles. Young couples prefer to have two children, regardless of gender. The study concluded that, there is no significant evidence to suggest that poor families are more likely to experience gender imbalance, while families with sufficient means tend to be more “China-oriented” values.